2016
DOI: 10.5935/0100-4042.20160092
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for the Rapid Identification of Fungal Metabolites and the Discovery of the Antiviral Activity of Pyrenocine a and Harzianopyridone

Abstract: The isolation and identification of bioactive metabolites from complex extracts obtained from microbial growth media is a time consuming, costly, and labor-intensive task. A strategy to rapidly identify secondary metabolites isolated from extracts obtained from the culture media of marine-derived and endophytic fungal strains is described. Identification was achieved by HPLC-UV-MS and 1 H NMR analyses in combination with data obtained from the Dictionary of Natural Products. Among the compounds identified, (-)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
7
0
2
Order By: Relevance
“…Several quinones have anti-viral effects. Ióca et al (2016) found that naphthoquinoneimine (13) isolated from an Aspergillus strain and emodin (98) and ω-hydroxyemodin (=citreorosein) (104) isolated from Penicillium strains had moderate to strong activity against several vira (Avian metapneumovirus (AMPV), Bovine diarrhea virus (BVDV), Herpes Simplex Virus Type 1 (HSV-1)). Additionally, Huang et al (2017) found anti-viral effect against HSV-1 with the AQs aspergilol H (137) and I (138) isolated from A. versicolor.…”
Section: Quinones As Pharmaceuticalsmentioning
confidence: 99%
“…Several quinones have anti-viral effects. Ióca et al (2016) found that naphthoquinoneimine (13) isolated from an Aspergillus strain and emodin (98) and ω-hydroxyemodin (=citreorosein) (104) isolated from Penicillium strains had moderate to strong activity against several vira (Avian metapneumovirus (AMPV), Bovine diarrhea virus (BVDV), Herpes Simplex Virus Type 1 (HSV-1)). Additionally, Huang et al (2017) found anti-viral effect against HSV-1 with the AQs aspergilol H (137) and I (138) isolated from A. versicolor.…”
Section: Quinones As Pharmaceuticalsmentioning
confidence: 99%
“…One of the most common methods used to achieve the best separation of secreted specialized metabolites produced by fungi is reverse phase (C-18) chromatography since it is more than ideal to interact with polar and some non-polar metabolites [150,[180][181][182]. In some cases, before injecting samples on LC, samples are needed to be purified on small solid phase extraction (SPE) columns to remove chromatography-impairing lipids and phospholipids [147,148,183].…”
Section: Identification Of Non-volatile Compounds Of Fungal Originmentioning
confidence: 99%
“…One strain, Pseudovibrio denitrificans Ab134, was further shown to produce bromotyrosine-derived alkaloids, which have been previously isolated exclusively from marine sponges [59]. Nevertheless, compounds obtained from fungal and bacterial communities associated with marine sponges have been evaluated majorly for anti-inflammatory, antibiotic, antiviral, and cytotoxic activities; however, the observed cytotoxicity on cancer cells was not very stimulating, and most of isolated compounds were further studied for antiviral properties [60][61][62][63]. Indeed, a role of microbial sponge symbionts in the production of cytotoxic compounds that can be potentially applied in anticancer therapies remains to be better studied and evaluated.…”
Section: Isolated Compoundmentioning
confidence: 99%